Analysis and Reflections on VIAF, Virtual International Authority File - Giulia Manzotti (JLIS.it, 2010)
The Virtual International Authority File (VIAF) is a joint experiment of the Library of Congress (LC), the Deutsche Nationalbibliothek (DNB), and the Bibliothèque Nationale de France (BNF) with Online Computer Library Center (OCLC). Started in 2000, VIAF is a linking between authority records of the participant national agencies, that are freely on the net through a global authority service, and provided with crush algorithms.